Competência social, problemas internalizantes e externalizantes de adolescentes de Cuiabá-MT : estudo de métodos mistos - Santos Junior, Darci Francisco dos (2025)
Introduction: Adolescence corresponds to the age group from 12 to 18 years old, an age in which an intense process of biopsychosocial growth and development occurs, such as the improvement of social skills, but in which the development of mental suffering manifested through internalizing and externalizing problems can also occur. Thus, knowledge of internalizing and externalizing skills and problems is of utmost importance to direct future strategies for the mental health of this population. Objective: To analyze the relationship between internalizing and externalizing problems and the Social Competence of adolescents from public schools in the Central-West region of Brazil, integrating quantitative and qualitative data to understand patterns and perceptions about this phenomenon. Methods: This is a mixed study with a concomitant embedded design of a dominant model, carried out with adolescents between 12 and 18 years old from state schools in Cuiabá-MT, from March 2021 to December 2022. A sociodemographic questionnaire, the Youth Self-Report instrument, and a concomitant interview were applied. Quantitative data were tabulated in Excel and analyzed using SPSS software, while qualitative data were processed using Braun and Clarke's Thematic Analysis. Results: The univariate correlational analysis showed significant correlations between total competences and internalizing problems (r= -0.12), as well as between isolation/depression (r=-0.002) and somatic problems (r=-0.12). The multivariate analysis identified an association between isolation and depression with social competence (r=0.003). All of these correlations were weak and negative, demonstrating that as the scores of these problems increase, the scores of total competences of adolescents decrease. Regarding the clinical scores of the main variables discussed in the study, Isolation/Depression presented 13.5%; Somatic Problems 13.1%; Internalizing Problems: 12.2% and Competence 10.0%. The study presented six categories, four of which are related to internalizing problems; one to externalizing problems; and one related to social competence. The population studied presented higher normative scores of social competence in relation to other regions of the country. Final Considerations: The results of this study highlight the importance of developing intervention strategies and public mental health policies aimed at youth with the aim of promoting health and minimizing the worsening of internalizing and externalizing problems.